Use of a Non-Pharmacological Pain Relief Kit to Reduce Opioid Use Following Orthopedic Surgery: A Prospective Randomized Study - Denis J O'Hara; Timothy F Tyler; Malachy P McHugh; Susan Y Kwiecien; Tyler Bergeron (International Journal of Sports Physical Therapy)
# Introduction